NILAI-NILAI PENDIDIKAN ISLAM YANG TERKANDUNG DALAM TARI RATÉB MEUSEUKAT - Intan Qurratul Aini (Jurnal Ilmiah Didaktika, 2016)
Ratéb Meuseukat is one of the variety of dance in Aceh; its lyrics and songs contain the messages of Islamic education, moral values, as well as direction to take a better life. Ratéb Meusekat dance is interesting to be studied because it is a folk dance that serves not only as an entertainment tool, but also as a media of Islamic Education. The researcher applied the descriptive–qualitative approach in this research that was intended to describe the presentation form and the messages contained in the Ratéb Meusekat dance. As data collecting method, the researcher did the observation, interview and document recording. In this study the researcher directly observed the process of Ratéb Meusekatdance in Lempia studio. The result of this research indicated that the Ratéb Meusekat dance contained of Islamic Educational messages by means the value of faith such as always remember Allah SWT, selawat to our Prophet and remember death. The value of worship is reflected in always being grateful;Then the message of moral valuecan be done by, for example,honoring the guest; The last value is the social relationship that can be applied by obeying the rule and by honoring the hero.